Tablet-based sensorimotor home-training system for amnestic mild cognitive impairments in the elderly: design of a randomised clinical trial - Bekrater-Bodmann, Robin; Löffler, Annette; Silvoni, Stefano; Frölich, Lutz; Hausner, Lucrezia; Desch, Simon; Kleinböhl, Dieter; Flor, Herta (BMJ open, 2019)
Introduction: Dementia (particularly Alzheimer’s disease, AD) is a major cause of impaired cognitive functions in the elderly. Amnestic mild cognitive impairment (aMCI) is a prodromal stage of AD, if substantiated by Alzheimer biomarkers. A neuroscientific model of pathological ageing emphasises the loss of brain plasticity, sensorimotor capacities and subsequent cognitive decline. A mechanistic treatment targeting dysfunctional plastic changes associated with ageing should be efficacious in delaying AD. In this trial, we aim to evaluate the effectiveness of a newly developed sensorimotor training, delivered at home, combined with personalised reinforcement, on the progression of aMCI-related cognitive impairments. - Methods and analysis: In a randomised trial, we will compare two aMCI groups (30 subjects each), randomly allocated to a sensorimotor or a cognitive control training. Both trainings consist of an adaptive algorithm, and will last 3 months each. We hypothesise that both trainings will have positive effects on cognitive function with the sensorimotor training being superior compared with the control training based on its improvement in basic perceptual skills underlying memory encoding and retrieval. The primary outcome is episodic memory function, improved hippocampal function during memory tasks will be a secondary outcome. As further exploratory outcomes, we expect improved segregation in sensory and motor maps, better sensory discrimination only in the sensorimotor training and reduced transition to dementia (examined after completion of this study). We expect the experimental training to be evaluated more positively by the users compared with the cognitive training, resulting in reduced rates of discontinuation. - Ethics and dissemination: The Ethics Committee of the Medical Faculty Mannheim, Heidelberg University, approved the study (2015-543N-MA), which adheres to the Declaration of Helsinki. The results will be published in a peer-reviewed journal. Access to raw data is available on request. - Trial registration number DRKS00012748.